The effect of pulse welding parameters on weld geometry of boron steel using low power fibre laser - Khairul Ihsan, Yaakob; M., Ishak; Siti Rabiatull Aisha, Idris (Faculty Mechanical Engineering, UMP, 2017)
Demands of tailored weld blank application on press hardened materials such as boron steel have given interest in the process parameter study of laser welding. The pulse wave mode of laser welding produces high peak power, replacing the continuous wave mode which could lead to wider applications. Due to complications on the process parameter of PW mode, the study of parameter effect is needed. In this paper, the effect of PW welding parameters on weld geometry of boron steel using Fibre laser is presented. Pulse overlap (PO), peak power (PP), pulse duration (PD) and pulse repetition rate are the common process parameters for PW mode used in this study. The bead on plate welding was conducted on uncoated boron steel and observation on width and depth of penetration was done. Based on the results, the higher PO produced deeper penetration and also a bad weld appearance. The effective pulse energy and effective peak power density were the result of the actual condition in pulse seam weld related with overlapping index generated from PO condition. The PP and PD were the related parameters that affected the energy of the beam, giving a significant effect on weld width and penetration. The energy of the beam showed the significance on weld geometry in low peak power laser application and the value will increase with the increase of PD. In contrast, PRR had no significant effect on weld geometry. The constant pulse overlap parameter produced constant energy applied for each pulse which led to no effect on weld geometry.